(E)-2-(5-Chloro-2-hydroxybenzylidene)-N-cyclohexylhydrazine- 1-carbothioamide - Arafath, Md. Azharul; Adam, Farook; Razali, Mohd. R. (International Union of Crystallography, 2017)
In the title compound, C14H18ClN3OS, the phenol ring is almost coplanar with the hydrazinecarbothioamide moiety, making a dihedral angle of 6.92 (8). The cyclohexane ring has a chair conformation and the conformation about the C N bond is E. In the crystal, molecules are linked by N—H O and O— H S hydrogen bonds, forming inversion dimers with an R2 2(14) ring motif flanked by two R2 2(6) ring motifs. The dimers are linked by short Cl Cl interactions, forming layers parallel to the ab plane.